A relaxed structural mechanics and fuzzy control for fluid–structure dynamic analysis. Issue 7 (12th August 2019) - Chen, Tim; Khurram, Safiullahand; Cheng, CYJ
Abstract : Purpose: This paper aims to deal with the problem of the global stabilization for a class of tension leg platform (TLP) nonlinear control systems. Design/methodology/approach: It is well-known that, in general, the global asymptotic stability of the TLP subsystems does not imply the global asymptotic stability of the composite closed-loop system. Findings: An effective approach is proposed to control chaos via the combination of fuzzy controllers, fuzzy observers and dithers. Research limitations/implications: If a fuzzy controller and a fuzzy observer cannot stabilize the chaotic system, a dither, as an auxiliary of the controller and the observer, is simultaneously introduced to asymptotically stabilize the chaotic system. Originality/value: Thus, the behavior of the closed-loop dithered chaotic system can be rigorously predicted by establishing that of the closed-loop fuzzy relaxed system.